Back to Black. (24th October 2014) - Calosi, Claudio; Varzi, Achille C.
Abstract: This is a brief sequel to Max Black's classic dialogue on the Identity of Indiscernibles. Interlocutor A defends the bundle theory by endorsing the (by now popular) view according to which Black's world does not contain two indiscernible spheres but rather a single, bi‐located sphere. His opponent, B, objects that A cannot distinguish such a world from a world with a single, uniquely located sphere, hence that the view in question adds nothing to A 's original response to Black's challenge. A is simply denying that there can be worlds with two or more indiscernible entities.